Inside the Mindful Mind: How Mindfulness Enhances Emotion Regulation Through Improvements in Executive Control. (December 2013) - Teper, Rimma; Segal, Zindel V.; Inzlicht, Michael
Although the psychological benefits of mindfulness training on emotion regulation are well-documented, the precise mechanisms underlying these effects remain unclear. In the present account, we propose a new linkage between mindfulness and improved emotion regulation—one that highlights the role played by executive control. Specifically, we suggest that the present-moment awareness and nonjudgmental acceptance that is cultivated by mindfulness training is crucial in promoting executive control because it increases sensitivity to affective cues in the experiential field. This refined attunement and openness to subtle changes in affective states fosters executive control because it improves response to incipient affective cues that help signal the need for control. This, in turn, enhances emotion regulation. In presenting our model, we discuss how new findings in executive control can improve our understanding of how mindfulness increases the capacity for effective emotion regulation.